Cutting-edge microangio-CT: new dimensions in vascular imaging and kidney morphometry - Hlushchuk, Ruslan; Zubler, Cédric; Barré, Sébastien; Shokiche, Carlos Correa; Schaad, Laura; Röthlisberger, Raphael; Wnuk, Monika; Daniel, Christoph; Khoma, Oleksiy; Tschanz, Stefan A.; Reyes, Mauricio; Djonov, Valentin (American Journal of Physiology-Renal Physiology, 2017)
In the last decades the contrast-enhanced microCT-imaging of whole animal kidney became increasingly important. The visualization was mainly limited to middle-sized vessels. Since modern desktop microCT-scanners provide the necessary detail resolution, we developed an approach for rapid visualization and consistent assessment of kidney vasculature and glomeruli number. This method is based on ?Angiofil®, a new polymerizing contrast agent with homogenous X-ray absorption, which provides continuous filling of the complete vasculature and enables correlative imaging approaches. For rapid and reliable kidney morphometry the microangioCT-datasets from GDNF+/- mice and their wildtype littermates were used. The results were obtained much faster compared to the current gold standard, histology-based stereology, and without processing artefacts. The histology-based morphometry was afterwards done on the same kidneys. Both approaches revealed that the GDNF+/- male mice had more than 30% fewer glomeruli. Futhermore, our approach allows defining sites of interest for further histological investigation, i.e., correlative morphology. The polymerized ?Angiofil stays in perfused vessels and is auto-fluorescent what greatly facilitates matching of histological sections with microangioCT-data. The presented approach is time-efficient and reliable qualitative and quantitative methodology. Besides glomerular morphometry the microangioCT-data can be used for qualitative and quantitative analysis of the kidney vasculature and correlative morphology.
EVALuna2:25561